Al-Istirātījyyat fī Takwīn al-Bī’ah al-Luġawiyyah li Rafʿi Qudrah al-Țalabah ʿalā Mahārah al-Kalām al-ʿArabī - Izzat Amini; Mohammad Arif Nurmuzib (JICALLS: Journal of Arabic Education, Linguistics, and Literature Studies, 2023)
The purpose of this study is to understand the strategies strategy of creating the language environment to raise the ability of students to speak and know how the language environment affects the Arabic language skills. This study adopts qualitative research methods and collects data in the form of interviews, observations and documents. The data analysis method used by researchers in the research is to analyze nonverbal data to verify the effectiveness of the data used by researchers. These data are undoubtedly original, and are widely used for participation, persistence, observation and triangulation. As for the results of this study, As for the strategy in creating the language environment in all institutes, it is to find a program that is implemented continuously every day, week, monthly or yearly. From a procedural point of view, the language center of the institution coordinates the language centers in all the institutes. As for the effect of the formation of the linguistic environment, it is that the students in the Islamic Teacher Education and the Arabic Language Tahfi Institute for the Qur'an are able to communicate. The language center has special goals, which are to make students fluent in speaking the Arabic language.